Obesity Status and Colorectal Cancer Screening in the United States. (3rd April 2013) - Kendall, Karima A.; Lee, Euni; Zuckerman, Ilene H.; Simoni-Wastila, Linda; Daniel, Marlon; Green, Pauline M.; Adderley-Kelly, Beatrice; Wutoh, Anthony K.
Abstract : Background . Findings from previous studies on an association between obesity and colorectal cancer (CRC) screening are inconsistent and very few studies have utilized national level databases in the United States (US). Methods . A cross-sectional study was conducted using data from the 2005 Medicare Current Beneficiary Survey to describe CRC screening rate by obesity status. Results . Of a 15, 769 Medicare beneficiaries sample aged 50 years and older reflecting 39 million Medicare beneficiaries in the United States, 25% were classified as obese, consisting of 22.4% "obese" (30 ≤ body mass index (BMI) < 35) and 3.1% "morbidly obese" (BMI ≥ 35) beneficiaries. Almost 38% of the beneficiaries had a body mass index level equivalent to overweight (25 ≤ BMI < 30). Of the study population, 65.3% reported having CRC screening (fecal occult blood testing or colonoscopy). Medicare beneficiaries classified as "obese" had greater odds of CRC screening compared to "nonobese" beneficiaries after controlling for other covariates (OR adj = 1.25; 95% CI: 1.12–1.39). Conclusions . Findings indicate that obesity was not a barrier but rather an assisting factor to CRC screening among Medicare beneficiaries. Future studies are needed to evaluate physicians' ordering of screening tests compared to screening claims among Medicare beneficiaries to better understand patterns of patients' and doctors' adherence to national CRC screening guidelines.